Channel allocation for hot spot areas in HAPS communication based on the prediction of mobile user characteristics. Issue 4 (1st October 2016) - Guan, Mingxiang; Wang, Le; Chen, Liming
Abstract: High altitude platform station (HAPS) communication employs multiple high altitude platforms with the same bandwidth in order to serve the same region. This working mode greatly increases user capacity and improves frequency spectrum utilization, thus endowing HAPS communication with its superiority in solving hot spot issues. In this study, a standard for deciding the minimum distance in mobile user access systems was derived. Using this standard, channel allocation approaches based on the prediction of user number change and call volume change were proposed. These proposed approaches could effectively remove the problem of insufficient or wasted channels caused by the lack of proactive cooperation in conventional channel allocation methods. These approaches are validated through simulation, in which the proposed channel allocation approaches demonstrated the reasonable allocation of channels and the avoidance of call blocking while improving the utilization of channels.